Menentukan Kebutuhan Material Penyemenan Plug Pada Trayek 26” Lapangan “PAS” Sumur “ASY” - Aly Rasyid; M. Mahlil Nasution; Phillip Asy Syams (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
Drilling operations are one of the most vital operations in supporting the oil and gas production efforts of a field. Cement plug or plugging is a term used in the oil and gas industry to refer to the process of cement well plugs in drilling wells that have various purposes, these cement plugs can be installed at various depths in the well. This research was conducted with several methodologies from the type of research, data collection techniques, data analysis, and data processing. In the process of cementing the 26